2014
DOI: 10.4081/ijas.2014.3227
|View full text |Cite
|
Sign up to set email alerts
|

Protection Conferred by a Live Avian Metapneumovirus Vaccine when Co-Administered with Live La Sota Newcastle Disease Vaccine in Chicks

Abstract: This paper examines the effects on specific pathogen-free (SPF) chicks when avian metapneumovirus (aMPV) and Newcastle disease virus (NDV) La Sota strain vaccines are co-administered. Day-old SPF chicks were divided into five groups. The first group was inoculated with sterile water (SW) and the rest of the groups were inoculated with live NDV vaccine VG/GA by the oculo-oral route. At 21 days-old, the unvaccinated chicks were again inoculated with SW. The four VG/GA-vaccinated groups were further inoculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Gelb et al (2007) demonstrated how NDV immunity decreased when combined with an IBV Arkansas vaccine in broiler chickens [7]. With the introduction of aMPV in 1990 0 s, the possibility of heterologous co-vaccination of NDV + aMPV and IBV + aMPV at day-old was investigated [19][20][21][22][23]. These publications showed that simultaneous administration of aMPV vaccine alongside NDV or IBV vaccine were compatible, with protection against virulent IBV, NDV or aMPV remaining uncompromised.…”
Section: Introductionmentioning
confidence: 99%
“…Gelb et al (2007) demonstrated how NDV immunity decreased when combined with an IBV Arkansas vaccine in broiler chickens [7]. With the introduction of aMPV in 1990 0 s, the possibility of heterologous co-vaccination of NDV + aMPV and IBV + aMPV at day-old was investigated [19][20][21][22][23]. These publications showed that simultaneous administration of aMPV vaccine alongside NDV or IBV vaccine were compatible, with protection against virulent IBV, NDV or aMPV remaining uncompromised.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to enhance the likelihood of detecting aMPV, farms were narrowed down to those with respiratory problems. Due to the relatively short viral shedding time [25,26], respiratory swabs or respiratory organs were collected from chickens showing mild to severe clinical signs from each farm. For blood collection, chickens less than three weeks old were excluded owing to the potential for maternal-derived aMPV-specific antibodies [27].…”
Section: Farm Selection Sample Collection and Processingmentioning
confidence: 99%
“…The detection rates of aMPV in northern Vietnam (17.2%) demonstrated a similar low prevalence to other countries. Three main possibilities for the low aMPV detection rates were: (i) aMPV poorly replicated in the respiratory tract of chickens compared to turkeys [45,46], (ii) relatively short viral shedding time (within one week post-infection) [25,26], and (iii) low level of viral shedding (the highest was about 10 2.7 TCID 50 /mL) [25]. Additionally, the sensitivity of the RT-PCR assay was known to affect the virus-detection results.…”
Section: The Detection Rates Of Ampv Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newcastle disease (ND) is a widespread, highly contagious viral disease, and causes severe economic losses to poultry industry (Ahmed et al 2007;Miller et al 2010;Ganapathy et al 2014). Over the past decades, intensive vaccination programmes against ND have been practised widely (Xiao et al 2009).…”
Section: Introductionmentioning
confidence: 99%